Selective JAK3 Inhibitors with a Covalent Reversible Binding Mode Targeting a New Induced Fit Binding Pocket. Issue 11 (17th November 2016) - Forster, Michael; Chaikuad, Apirat; Bauer, Silke M.; Holstein, Julia; Robers, Matthew B.; Corona, Cesear R.; Gehringer, Matthias; Pfaffenrot, Ellen; Ghoreschi, Kamran; Knapp, Stefan; Laufer, Stefan A.
Summary: Janus kinases (JAKs) are a family of cytoplasmatic tyrosine kinases that are attractive targets for the development of anti-inflammatory drugs given their roles in cytokine signaling. One question regarding JAKs and their inhibitors that remains under intensive debate is whether JAK inhibitors should be isoform selective. Since JAK3 functions are restricted to immune cells, an isoform-selective inhibitor for JAK3 could be especially valuable to achieve clinically more useful and precise effects. However, the high degree of structural conservation makes isoform-selective targeting a challenging task. Here, we present picomolar inhibitors with unprecedented kinome-wide selectivity for JAK3. Selectivity was achieved by concurrent covalent reversible targeting of a JAK3-specific cysteine residue and a ligand-induced binding pocket. We confirmed that in vitro activity and selectivity translate well into the cellular environment and suggest that our inhibitors are powerful tools to elucidate JAK3-specific functions. Graphical Abstract: Highlights: Identification and characterization of novel covalent reversible JAK3 inhibitors Picomolar affinities along with both high isoform and kinome selectivity is achieved Covalent-reversible interaction and a new induced binding pocket confirmed by X-ray structures High potency and selectivity are successfully proven in cellular models Abstract : JAK1/3 signaling plays a major role in immunological and inflammatory processes, but the reciprocal dependency of this receptor-sharing kinase pair still remains unclear. Forster et al. report highly selective covalent reversible JAK3 inhibitors as promising tools to elucidate this issue.